Patients with History of Intravenous Drug Use (IDU) with Septic Arthritis of the Foot and Ankle Have Suboptimal Hospitalization Outcomes Compared to Patients Without IDU - Margaret Shields MD; Alex Toppo; Mariano Menendez Furrer MD; Peter Dewire MD; Matthew Salzler MD (Foot & Ankle Orthopaedics, 2019)
Category: Infection Introduction/Purpose: Although intravenous drug use (IDU) is a known risk factor for septic arthritis of the foot and ankle (F&A), little is known about its influence on hospitalization outcomes. This study evaluated differences in demographic characteristics and hospitalization outcomes of septic arthritis of the F&A according to IDU status. Methods: Using the Nationwide Inpatient Sample for the years 2000 to 2013, we identified all patients aged 15-64 with a principal discharge diagnosis of septic arthritis of the F&A. Applying previously published algorithms, septic arthritis of the F&A was classified as related or unrelated to IDU. We assessed differences in demographic characteristics and in-hospital outcomes including length of hospital stay (LOS), leaving against medical advice (AMA), hospital charges, and presence or absence of surgical intervention. Results: Of the 14,198 hospitalizations, 11% were associated with IDU. Patients with IDU were more likely to be younger, black, and have Medicaid or no insurance coverage. Patients with IDU were more likely to leave AMA (9.7% vs 1.4%, p<0.001), have longer LOS (9.2 vs 6.8 days, p<0.001), and incur increased hospital charges ($58,628 vs $38,876, p=0.005). In addition, patients with IDU were significantly less likely to receive an arthroscopy (1.5% vs 6.5%, p<0.001) or arthrotomy (2.2% vs 11.0%, p<0.001) of the foot. Conclusion: IDU-related septic arthritis of the foot and ankle is associated with suboptimal hospitalization outcomes and greater resource use. Given the disparity in outcomes, there is potential to improve outcomes of septic arthritis of the foot and ankle in patients with IDU via enhanced physician communication skills among disenfranchised patient populations and proactively addressing substance abuse issues early during hospital admission.